Using Behavioral Economics to Reduce the Value-Action Gap (Ökologisches Wirtschaften - Fachzeitschrift, 2020)
Research and practice have long been concerned with the questions of how to reduce climate-damaging emissions and promote sustainable behavior. Although many people have good intentions to reduce their carbon footprint, this rarely affects their actual behavior. By combining findings from value-action-gap research and approaches from behavioral economics, we show how new instruments can foster sustainable actions.